Police’s Investigation Outside the National Investigation Budget: The Sekayam Police District Policy - Aleksander Sebayang; Joko Martono; Purwanto Purwanto (Proceedings of AICS - Social Sciences, 2018)
The State requires funds in carrying out the duties of the implementation of duties and responsibilities. Funds needed to finance the execution those duties and responsibilities are planned in the draft budget which contains expenditures and receipts in a year accompanied by financial administration. Furthermore, the state activities to be carried out by its apparatus, basically have been planned for a dissertation of the required cost. The state apparatus of investigators in carrying out their duties and responsibilities as well, the cases handled must be budgeted in the current year in terms of both the amount and the cost. The act of the investigator to seek and collect evidence which with that evidence makes light of the criminal offense and to find the suspect in need of fund. The investigation budget in the National Police (Polri) uses an index system. Budget support for criminal investigation and investigation activities, i.e. cases of extreme, difficult, moderate, and easy. Polri's investigation budget is so small that sometimes it is not enough to handle a case, especially in remote areas that are difficult to reach. This study is a normative juridical research, where the data used in this study is secondary data in the form of books, legislation, documents and other writings relating to the problems under investigation. Based on this research revealed that the Policies should be taken by Sekayam Police District, Sanggau, West Kalimantan province to keep handling crimes that exceed the number of cases and exceed the budget funds in the year concerned. The policy is legally to be done, since the number of crimes that occur cannot be predicted in number, and must be completed in accordance with applicable regulations. The efforts by Sekayam Police District to overcome the cost of investigation that exceed the budget allocation of criminal case handling is done by proposing to District Police (Polresta) Sanggau. Policies by the Sekayam Police to deal with criminal offenses that exceed the number of cases and exceed the budgetary funds in the relevant year have implications to administrative accountability.Keywords:police budget, investigationbudget, budget policy.